2023
DOI: 10.3389/fphar.2023.1110146
|View full text |Cite
|
Sign up to set email alerts
|

Second generation androgen receptor antagonist, TQB3720 abrogates prostate cancer growth via AR/GPX4 axis activated ferroptosis

Abstract: Purpose: Prostate cancer (PCa) poses a great threat to humans. The study aimed to evaluate the potential of TQB3720 in promoting ferroptosis to suppress prostate cancer, providing a theoretical basis for PCa therapy.Methods: PCa cells and nude mice models were divided into TQB3720, enzalutamide (ENZ), and control groups. Sulforhodamine B assay, colony formation assessment, organoids culture system, and the CCK8 assay were used for detecting proliferation. Western blot assay was processed to detect the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Additionally, recent studies have shown that small molecular reagents, including N-acetylcysteine (NAC), dapagliflozin and salusin-β, can effectively improve renal function and alleviate kidney injury by suppressing ferroptosis. It has also been reported that many Chinese herbal components, such as glabridin [128], umbelliferone [129], schisandrin A [130], ginkgolide B [131], calycosin [132], quercetin [133], vitexin [134], dapagliflozin [135] and platycodin D [136], can effectively inhibit the oxidative stress and ferroptosis of renal tubular epithelial cells and thus exert a positive effect on improving renal function in DKD.…”
Section: Diabetic Kidney Disease (Dkd)mentioning
confidence: 99%
“…Additionally, recent studies have shown that small molecular reagents, including N-acetylcysteine (NAC), dapagliflozin and salusin-β, can effectively improve renal function and alleviate kidney injury by suppressing ferroptosis. It has also been reported that many Chinese herbal components, such as glabridin [128], umbelliferone [129], schisandrin A [130], ginkgolide B [131], calycosin [132], quercetin [133], vitexin [134], dapagliflozin [135] and platycodin D [136], can effectively inhibit the oxidative stress and ferroptosis of renal tubular epithelial cells and thus exert a positive effect on improving renal function in DKD.…”
Section: Diabetic Kidney Disease (Dkd)mentioning
confidence: 99%
“…The expression of Ki-67, NAR6A1, and FASN in xenograft tumors was examined using IHC staining as our previous reports. [24,25] Briefly, paraffin-embedded tumor sections were deparaffinized and rehydrated. was performed by heating the sections in citrate buffer (pH 6.0) using a microwave.…”
Section: Free Fatty Acid Assaymentioning
confidence: 99%
“…It is widely found in several edible plants, including hawthorn, buckwheat, mung bean, millet, and Passiflora species. [1][2][3] Vitexin is a C-glycoside flavonoid with a stable bond between its aglycone and sugar moiety. Due to this structural characteristic, C-glycosides like vitexin are more stable than O-glycosides and less likely to undergo hydrolysis, which main-tains its structural integrity.…”
Section: Introductionmentioning
confidence: 99%